Aus Klinik und Praxis: Objektbeziehung und Performanz - zur relationalen Dynamik der Libido - Egloff, Götz (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2012)
Summary Object Relations and Performance: On the Relational Dynamics of the Libido The essay depicts the therapeutic process of a psychodynamic short term child therapy, containing thoughts on object relations and performativity. During therapy, object internalizations emerge and manifest themselves through enactments inside and outside the therapeutic relationship. The subsiding of the patient´s mild depressive symptom, which carries imprints of oedipality, is outlined by means of psychodynamic and performative concepts, these focusing on subject orientation. Pathology oriented understanding gives way to few interventions whilst play and conversation are taking place within the therapeutic relationship. The transformation of the symptom toward restitutio ad integrum primarily takes place through the performance within the relational process. The interpretative work is close to consciousness and solution oriented, carrying uncovering aspects. By means of biographical work, contextualizations of problems and propositions of interpretation with the patient´s mother, the patient´s experiencing as well as others´ views on her change. She begins to see herself, and begins to be seen, more and more in terms of a subject of active autonomy rather than of an object of passive victimhood. This process takes place within a period of eight months. At the end, for the patient´s further developmental process, restitutio ad integritatem can be expected.